Union Wage Policy and the Supply of Labor - Ulman, Lloyd (Quarterly Journal of Economics, 1951)
I. Introduction, 237. — II. The union's "optimum" wage rate, 239. — III. Absorption of unemployment: backward-rising supply curve of man-hours, 244. — IV. Maximization by unions and business firms, 250.